Evaluation of E-Learning Implementation During the Covid-19 with the DeLone and McLean Models - Nariza Wanti Wulan Sari; Wahyu Yanuartha; Muhammad Yani; Sulfikar Rakita Dewa (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2021)
During the Covid pandemic the learning process was carried out using e-learning media. SMK TI Airlangga Samarinda is one of the schools that has used e-learning in its learning process both before the Covid pandemic. Furthermore, an evaluation of the success of e-learning implementation will be carried out using the DeLone and McLean information system success model (D&M IS Success Model). In this model, there are six measurement variables, namely system quality, information quality, service quality, usage, user satisfaction, and net benefits. The purpose of this study is to provide an overview of the use of e-learning at SMK TI Airlangga Samarinda to the school and to find out the factors that influence the successful implementation of e-learning at SMK TI Airlangga Samarinda. To achieve this goal, SEM-PLS analysis (structural equation model - partial least square) is used. The subjects used were 336 students of SMK TI Airlangga Samarinda. The sampling technique used in this study was purposive sampling, with consideration of the availability of data obtained a sample of 192. Data collection techniques in this study using questionnaires, interviews, and literature study. The results of this study indicate that the quality of information and system quality in e-learning has a positive effect on the satisfaction of using e-learning which in turn has an effect on the benefits felt by students while using e-learning. In addition, the quality of the e-learning system also has a positive effect on the intensity of e-learning use, which means that the better the quality of the system will increase the intensity of e-learning use.